Nghiên cứu thành phần hóa học cây Chay (Artocarpus lakoocha Roxb.). Phần II. Các hợp chất triterpen, steroid và monoglyxerit - Bảo, Nguyễn Chí; Anh, Nguyễn Thị Hoàng; Sung, Trần Văn (Vietnam Journal of Chemistry, 2012)
Three compounds were isolated from the n-hexane and ethyl acetate extracts of Artocarpus lakoocha collected in Son La province. Their structures were elucidated as friedelane-3-one, stigmast-4-ene-3-one and 1-tricosanoyl-glycerol by analysis of MS, NMR spectra and comparison with the published data.